PENGARUH PELAKSANAAN SENSUS PAJAK NASIONAL, KUALITAS PELAYANAN DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Wajib Pajak Orang Pribadi di KPP Pratama batu) - Mareta, Emielia (Jurnal Mahasiswa Perpajakan, 2014)
National Tax Census is implemented to improve the obedience of taxpayers. The expected goals of National Tax Census include improving tax bases, increasing the obedience to submit Tax Annual Report, improving tax revenue, updating database, and socializing and educating taxpayers. Research type is explanatory. The sample includes private taxpayers who are subjected to National Tax Census and registered at KPP Pratama Batu. Sampling method is non-probability sampling with accidental sampling technique. Data analysis method involves descriptive analysis and multiple linear regression analysis. Result of research indicates that Fcount is 175,149 and Ftable is 2.45 (Fcount > Ftable). It is concluded that simultaneously, National Tax Census implementation service quality and tax knowledge have significant influence on the obedience of taxpayers. Result of dominant test with Standardized Coefficients Beta has indicated that National Tax Census implementation has beta of 0.220, while service quality and tax knowledge have 0.275 and 0.617 for their betas. Based on these results, it can be said that the most dominant variable influencing the obedience of taxpayers is tax knowledge. Keywords : The Obedience of Taxpayers, National Tax Census Implementation, Service Quality, Tax Knowledge